Antibacterial and antioxidant activities in Homalomena joseffi boyce and wong extract and its phytochemicals - Radu, Kimberley Rinai (2020)
Poisonings donned from consuming daily dietary products ranging from carbohydrates to fibrous foods is a common problem faced by every country collectively. Mainly due to poor food handling, pathogenic strains are passed on from person to person causing growing concerns in the battle against antibiotic resistant bacteria. For many years the Homalomena species is widely used in treating various ailments in traditional medicine, ranging from headaches to bacterial infections in Asian countries such as India and China. Recently, more Homalomena species have been found within the tropical forests of Borneo, including Homalomena joseffi P.C. Boyce and S.Y. Wong. It serves as an alternative natural antimicrobial to the local people. The aims of this study were to determine antibacterial and antioxidant activities of H. joseffi crude extracts and its fractions and to analyse the phytochemical constituents in H. joseffi extracts. The dried rhizome of H. joseffi was extracted using maceration methods with methanol as a solvent. The crude extract then was fractionated using liquid-liquid fractions with solvents of hexane, chloroform, ethyl acetate and aqueous methanol. The antibacterial activity of the crude extract and its fractions were tested against selected foodborne pathogens in term of disc diffusion assay (DDA), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill curve assay using standard methods of Clinical and Laboratory Standard Institute (CLSI). The total phenolic compounds (TPC) in selected extract and fractions were analysed using the Folin-Ciocalteau method. The antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The active antibacterial compounds in crude and fractions were identified by Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS). Diameter of inhibition zones of crude extracts against selected foodborne pathogens were ranged from 9.33 ± 0.57 to 11.00 ± 0.57 mm. MICs of the crude extract were in the range of 0.31 to 5.00 mg/mL. The crude extracts can kill the tested bacterial with MBC values in the range from 0.63 to 5.00 mg/mL. Time-kill assay curve analyses results showed that the crude extracts were able to completely kill the bacterial growth at 4 × MIC at 4 hours. The total phenolic content in the crude extract was 432.138 GAE/g. While DPPH results displayed IC50 of the crude extract was 11.809 μg/mL of dried weight material. The inhibition zone of fractions from methanolic crude extract was ranged from 7.00 ± 0.00 mm to 12.50 ± 1.00 mm. The ii MICs of fractions were range from 0.156 mg/mL to 1.250 mg/mL. Moreover, the MBCs values of fractions were ranged from 0.625 mg/mL to 5.00 mg/mL. GC-MS analyses of the crude extract resulted nine major compounds which contribute to antibacterial activity, namely hotrienol, mullilam diol, palmitic acid, viridiflorol, neryl acetate, ethyl palmitate, globulol, linoleic acid and ethyl linoleate. Whereas its fraction consists of seven major compounds such as linalool, l-terpinen-4-ol, cryptone, α-terpineol, elemol, spathulenol and methyl palmitate. Furthermore, LC-MS has identified 11 non-volatile compounds, namely corymboside, ethylmorphine, abscisic acid, sinomenine, leucylproline, rhoifolin, glutethimide, indole-2-acrylic acid, umbelliferone, quercetin and scopletin. In conclusion, H. joseffi extract and its compounds display potential antibacterial activity against foodborne pathogens and antioxidant activity. Therefore, it could be developed and implemented as natural food preservatives.